Multi-center validation of the Bowel Injury Predictive Score (BIPS) for the early identification of need to operate in blunt bowel and mesenteric injuries. Issue 1 (January 2022) - Wandling, Michael; Cuschieri, Joseph; Kozar, Rosemary; O'Meara, Lindsay; Celii, Amanda; Starr, William; Burlew, Clay Cothren; Todd, S. Rob; de Leon, Alejandro; McIntyre, Robert C; Urban, Shane; Biffl, Walt L; et al.
Highlights: This prospective multicenter trial validates BIPS as a predictor of bowel injury requiring surgery. BIPS is easily calculated in the ED with 3 variables including CT scan, WBC, and physical exam. BIPS is a useful adjunct in the initial evaluation of trauma patients including those with altered mental status. Abstract: Introduction: The Bowel Injury Prediction Score (BIPS) is a tool for identifying patients at risk for blunt bowel and mesenteric injury (BBMI) requiring surgery. BIPS is calculated by assigning one point for each of the following: (1) WBC ≥ 17, 000, (2) abdominal tenderness, and (3) injury grade ≥ 4 (mesenteric contusion or hematoma with bowel wall thickening or adjacent interloop fluid collection) on CT scan. A total score ≥ 2 is associated with BBMI requiring surgery. We aimed to validate the BIPS as a predictor for patients with BBMIs requiring operative intervention in a multi-center prospective study. Materials and methods: Patients were prospectively enrolled at 15 U.S. trauma centers following blunt trauma with suspicion of BBMI on CT scan between July 1, 2018 and July 31, 2019. The BIPS was calculated for each patient enrolled in the study. Results: Of 313 patients, 38% had BBMI requiring operative intervention. Patients were significantly more likely to require surgery in the presence of abdominal tenderness (OR, 3.6; 95% CI, 1.6–8.0) and CT grade ≥ 4 (OR, 11.7; 95% CI, 5.7–23.7). Patients with a BIPS ≥ 2 were more than ten times more likely to require laparotomy than those with a BIPS < 2 (OR, 10.1; 95% CI, 5.0–20.4). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of a BIPS ≥ 2 for BBMI requiring surgery was 72% (CI 0.6–0.8), 78% (CI 0.7–0.8), 67% (CI 0.6–0.8), and 82% (CI 0.8–0.9), respectively. The AUROC curve for BIPS ≥ 2 was 0.75. The sensitivity, specificity, PPV, and NPV of a BIPS ≥ 2 for BBMI requiring surgery in patients with severe alteration in mental status (GCS 3–8) was 70% (CI 0.5–0.9), 92% (CI 0.8–1.0), 82% (CI 0.6–1.0), and 86% (CI 0.7–1.0), respectively. Conclusion: This prospective multi-center trial validates BIPS as a predictor of BBMI requiring surgery. Calculation of BIPS during the initial evaluation of trauma patients is a useful adjunct to help general surgeons taking trauma call determine operative versus non-operative management of patients with BBMI including those with severe alteration in mental status.